ERROR ANALYSIS ON DESCRIPTIVE PARAGRAPH MADE BY FIRST GRADE STUDENTS OF SMA NEGERI 4 MALANG - WARDANI, KARLINA SAPTA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Acquiring second language is not easy for the learners because they have to learn more about the rules of sentence structure in second language. Makingerror in acquiring second language is inevitable because the learners still use therules in their first language to transfer second language. Therefore, errors wereconsidered as being the result of the persistence of existing mother tongue habitsin the new language.This study is to investigate the students’ errors in descriptiveparagraph made by the first grade students of SMA N 4 Malang. The studentsoften make errors when they write a descriptive paragraph. The problems of thisstudy are what types of error found and what sources of error found in descriptiveparagraph. Meanwhile, the objectives of this study are to identify and classify thetypes of error found and to investigate the sources of error found. The method of this study is qualitative approach. This study was carriedout at SMA N 4 Malang. The populations of this study were the first gradestudents of SMA N 4 Malang in academic year of 2012/2013. The classes thatwere used as the sample were three classes in the first grade that were taught bythe same teacher.The technique used to analyze the data of this study is using thetheory of error analysis proposed by Dulay et al (1982). The steps of analyzingdata are collecting the data, identifying the error, describing the error, explainingthe error, and drawing the conclusion. The result of the study showed that based on surface strategy taxonomy,there were (37%) omissions errors,(21%) additions, (38%) misformations, and(4%) misorderings. Misformations error is the highest error occurred. The resultfor the sources of errors were interlingual transfer (18%), intralingual transferdivided in to four parts source of error, there were (9%) for overgeneralization, 1error for ignorance of rule restrictions, (22%) for incomplete application of rules,(40%) for false concept hypothesized, and (11%) for communication strategies.  This study is useful for the students and the teacher; it helps the teacher toknow the problems of the students in their writing. It is suggested that the firstgrade students of SMA N 4 Malang should be given intensive exercises on thecorrect structure in their writing and improve their writing to learn secondlanguage to know their mistake. It is necessary for the first year students and theteacher of SMA N 4 Malang to improve their teaching and learning process. Keywords: Error Analysis, surface Strategy Taxonomy, and Sources of Error